PHARMACEUTICAL ANALYTICAL STUDY OF PRATISARANEEYA TILANALA KSHARA - Dr.Shreekanth Tippannanavar, Dr.Veerayya R Hiremath, Dr. Shashikala, Dr.Gururaj N (EPRA International Journal of Research and Development (IJRD), 2024)
Introduction: Kshara is the alkali obtained from the processing and filtration of herbal drug ashes. Kshara karma is considered an anushastra in Ayurveda and is used in many Parasurgical procedures where shastras are difficult to perform. Kshara is mainly divided into paaneeya kshara and pratisaraneeya kshara based on the mode of administration and based on potency kshara is made to be mrudu, madyama and teekshna. The method of preparation is mentioned in the Sushrutha Samhita, asthanga hrudaya, sarangadhara Samhita, rasatarangini etc. Hence the present work pharmaceutico-analytical study on pratisaraneeya Tilanala kshara is undertaken. Aim and Objective: The main aim of the study is to prepare pratisaraneeya tilanala kshara as per the classical reference and Physico-chemical analysis of the same. Materials and methods: collection of Tila, preparation of ksharajala and obtaining the pratisaraneeya kshara. A comprehensive physico-chemical analysis of Tilanala kshara was done. Results: loss on drying, total ash value, acid insoluble, water-soluble, refractive index, and pH were found to be well within the normal range. Discussion and Conclusion: Adverse events and drug interactions can result in serious harm to patients and can also lead to increased healthcare costs. The present study asserts that Tilanala kshara is safe for therapeutic use which is substantial in the treatment of kshara Pratisarana.